Advanced Computing in Industrial Mathematics 12th Annual Meeting of the Bulgarian Section of SIAM December 20-22, 2017, Sofia, Bulgaria Revised Selected Papers - Georgiev, Krassimir; Todorov, Michail; Georgiev, Ivan (Studies in Computational Intelligence, 2019)
This book gathers the peer-reviewed proceedings of the 12th Annual Meeting of the Bulgarian Section of the Society for Industrial and Applied Mathematics, BGSIAM'17, held in Sofia, Bulgaria, in December 2017. The general theme of BGSIAM'17 was industrial and applied mathematics, with a particular focus on: high-performance computing, numerical methods and algorithms, analysis of partial differential equations and their applications, mathematical biology, control and uncertain systems, stochastic models, molecular dynamics, neural networks, genetic algorithms, metaheuristics for optimization problems, generalized nets, and Big Data. .